KECERDASAN EMOSIONAL TOKOH UTAMA DALAM MANGA GREAT TEACHER ONIZUKA KARYA TORU FUJISAWA - Putu Ayu Utami, Ni Luh (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Teacher Onizuka. The comic tell a story about a young man, 22 year old, who want to be a great teacher named Eikichi Onizuka.By using the theory of emotional intelligence by Daniel Goleman, this comic is analyzed from the point of view of main character emotional intelligence and impact to the other character. According to the result of analysis the emotional intelligence become a figure Onizuka in the comic are self awareness, self regulation, motivation, empathy, and social skills. The impact from his emotional intelligence are the student can tell the truth about her feeling, be confident and rigid, always go to school and also there is one student who become an artist. The emotional intelligence of Onizuka also has inspired other teachers although there are teachers who doesn’t like it. Beside, emotional intelligence of Onizuka makes someone more concerned with others. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Emotional Intelligence, main character, impact